Implementasi Program Literasi Digital Berbasis Smart Society 5.0 di Kabupaten Ciamis: Studi pada Dinas Komunikasi dan Informatika Kabupaten Ciamis - Nida Nurpadilah; Dini Yuliani; Regi Refian Garis (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to determine the implementation of the Smart Society 5.0-based digital literacy program in Ciamis Regency, implemented by the Communication and Informatics Office (Diskominfo). This program is part of the local government's digital transformation to create a smart, inclusive, and adaptive society to the development of information technology. This study uses a qualitative approach with descriptive methods, and data is obtained through in-depth interviews, field observations, and documentation. The analysis is conducted using Charles O. Jones's theory of public policy implementation, which includes three main components: organization, interpretation, and implementation. The results show that organizationally, Diskominfo has a supportive structure and relatively competent human resources, although there are still limitations in the mastery of digital technology among employees. From an interpretation perspective, the digital literacy strategy is implemented through public education, hoax prevention, digital content provision, and social media utilization. Meanwhile, in terms of implementation, supervision is carried out through monitoring, regular reporting, the use of digital applications, and evaluation forums. Some obstacles faced include budget limitations, the digital divide between regions, uneven technological infrastructure, and the lack of specific evaluation indicators. Nevertheless, improvement efforts continue through human resource training, optimization of digital facilities and infrastructure, and cross-sector synergy. This study concludes that the implementation of the Smart Society 5.0-based digital literacy program in Ciamis Regency has been quite successful, but still requires strengthening human resources, evaluation policies, and equitable digital access in rural areas.